Consistent analysis of the elastic, inelastic and fusión cross sections in the systems 16O + 144, 148, 150, 152Sm at sub-barrier energies - E. Guerra; J. Lubian; R. Cabezas (Tecnología en Marcha, 2016)
On the basis of the experimental data reported in the literature, an analysis of the elastic, inelastic and fusion cross sections was made for the 16O + 144, 148, 150, 152Sm systems at energies near the Coulomb barrier using a consistent deformed optical model potential. Coupled-channel calculations of the elastic and inelastic scattering cross sections were carried out using the ECIS87 code.